Protection and Controlled Gastrointestinal Release of Bromelain by Encapsulating in Pectin–Resistant Starch Based Hydrogel Beads - Mala, Thatchajaree; Anal, Anil Kumar (Frontiers in Bioengineering and Biotechnology, 2021)
Hybrid pectin and resistant starch based hydrogel beads loaded with bromelain using extrusion gelation method were prepared and evaluated to enhance the activity of bromelain during gastrointestinal passage and thermal processing. The solutions of pectin-resistant starch with bromelain were dropped into the gelation bath containing calcium chloride (0.2 M) solution to develop various types of hydrogel beads. The physicochemical characteristics of the synthetized hydrogel beads were evaluated. The ratio (4.5:1.5 w/w) of pectin and resistant starch concentration significantly (p < 0.05) enhanced the encapsulation efficiency (80.53%). The presence of resistant starch resulted in increased entrapment of bromelain, improved swelling properties with sustained release behavior and improved gastric stability than pectin hydrogels alone. The swelling of hydrogel beads were higher at pH 7.4 than pH 1.2. Optimized batch of hybrid pectin/ resistant starch exhibited spherical shape. Optical and scanning electron microscopy showed more packed and spherical shape from pectin/ resistant starch hydrogel bead network. Fourier transformation infrared spectroscopy was also used to confirm the presence of bromelain in the hydrogel beads. The encapsulated bromelain in the pectin/ hi-maize starch beads produced at a pectin/ hi-maize ratio of 4.5:1.5 (percent w/w; formulation P4) obtained the highest relative bromelain activity in all heat treatments including at 95 C, whereas the highest activity of free bromelain was found only at 30 C. Bromelain encapsulated in hydrogels released at a faster rate at simulated intestinal fluid (SIF, pH 7.4) than at simulated gastrointestinal fluid (SGF, pH 1.2)